What is wrong with post‐fire soil erosion modelling? A meta‐analysis on current approaches, research gaps, and future directions. Issue 1 (10th December 2020) - Lopes, A.R.; Girona‐García, A.; Corticeiro, S.; Martins, R.; Keizer, J.J.; Vieira, D.C.S.
Abstract: In the near future, a higher occurrence of wildfires is expected due to climate change, carrying social, environmental, and economic implications. Such impacts are often associated with an increase of post‐fire hydrological and erosive responses, which are difficult to predict. Soil erosion models have been proven to be a valuable tool in the decision‐making process, from emergency response to long‐term planning, however, they were not designed for post‐fire conditions, so need to be adapted to include fire‐induced changes. In recent years, there have been an increasing number of studies testing different models and adaptations for the prediction of post‐fire soil erosion. However, many of these adaptations are being applied without field validation or model performance assessment. Therefore, this study aims to describe the scientific advances in the last 20 years in post‐fire soil erosion modelling research and evaluate model adaptations to burned areas that aim to include: (i) fire‐induced changes in soil and ground cover; (ii) fire‐induced changes in infiltration; (iii) burn severity; and (iv) mitigation measures in their predictions. This study also discusses the strengths and weaknesses of these approaches, suggests potential improvements, and identifies directions for future research. Results show that studies are not homogeneously distributed worldwide, according to the model type used or by region most affected by wildfire. During calibration, 73% of cases involved model adaptation to burned conditions, and only 21% attempted to accommodate new processes. Burn severity was addressed in 75% of cases, whilst mitigation measures were simulated in 27%. Additionally, only a minor percentage of model predictions were validated with independent field data (17%) or assessed for uncertainties (13%). Therefore, further efforts are required in the adaptation of erosion models to burned conditions, to be widely used for post‐fire management decisions. © 2020 John Wiley & Sons, Ltd. Abstract : The application of post‐fire erosion models is not homogeneously distributed worldwide regarding the model type used or where larger areas are affected. Further efforts are required in the adaptation of erosion models to burned conditions, addressing post‐fire infiltration, burn severity, and post‐fire mitigation measures. Future studies on post‐fire soil erosion modelling could consider using a multidisciplinary model combination as well as including uncertainty analysis in predictions for better communication of the scientific outputs.